Durkheim’s Social Solidarity: Learning from the COVID-19 Pandemic through the ‘Jogo Tonggo’ Policy - Wijanarka, Tunjung; Suma, Medina Safira; Azis, Muhammad Abdul; Sesar, Yuve Kukuh (Journal Public Policy, 2023)
This paper attempts to discuss the importance and necessity of social solidarity in societal structure during times of crisis. Learning from the conditions of the COVID-19 Pandemic in Indonesia, particularly in Central Java Province in 2019-2022, which continues to increase due to COVID-19 virus mutation into various variants such as Delta and Omicron, reveals a very concerning situation. When COVID-19 cases continued to rise in various cities and districts throughout Central Java, the Governor of Central Java, Ganjar Pranowo, issued a policy known as ‘Jogo Tonggo’ (Javanese), which translates to 'Take care of your neighbors' in Indonesian. This policy has been shown to be effective in assisting health workers and reducing the government’s burden in dealing with a pandemic. This paper will be analyzed through Emile Durkheim’s concept of Social Solidarity through a literature review, which can further demonstrate that social solidarity in Indonesian society has proven to function well as social resilience when a crisis such as the COVID-19 Pandemic occurs.